Nox2 underpins microvascular inflammation and vascular contributions to cognitive decline. Issue 7 (July 2022) - Alfieri, Alessio; Koudelka, Juraj; Li, Mosi; Scheffer, Sanny; Duncombe, Jessica; Caporali, Andrea; Kalaria, Rajesh N; Smith, Colin; Shah, Ajay M; Horsburgh, Karen
Chronic microvascular inflammation and oxidative stress are inter-related mechanisms underpinning white matter disease and vascular cognitive impairment (VCI). A proposed mediator is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 2 (Nox2), a major source of reactive oxygen species (ROS) in the brain. To assess the role of Nox2 in VCI, we studied a tractable model with white matter pathology and cognitive impairment induced by bilateral carotid artery stenosis (BCAS). Mice with genetic deletion of Nox2 (Nox2 KO) were compared to wild-type (WT) following BCAS. Sustained BCAS over 12 weeks in WT mice induced Nox2 expression, indices of microvascular inflammation and oxidative damage, along with white matter pathology culminating in a marked cognitive impairment, which were all protected by Nox2 genetic deletion. Neurovascular coupling was impaired in WT mice post-BCAS and restored in Nox2 KO mice. Increased vascular expression of chemoattractant mediators, cell-adhesion molecules and endothelial activation factors in WT mice post-BCAS were ameliorated by Nox2 deficiency. The clinical relevance was confirmed by increased vascular Nox2 and indices of microvascular inflammation in human post-mortem subjects with cerebral vascular disease. Our results support Nox2 activity as a critical determinant of VCI, whose targeting may be of therapeutic benefit in cerebral vascular disease.